Evaluating pre-consult patient education videos for patients with newly-diagnosed anal squamous cell carcinoma: Impact on patient comprehension, satisfaction and distress - Kelsey L. Corrigan; Lauren M. Andring; Prajnan Das; Cheryl Pfennig; Kimberly B. Porter; Ethan B. Ludmir; Sonal S. Noticewala; Bruce D. Minsky; Grace L. Smith; Eugene J. Koay; Albert C. Koong; Angelica Arzola; et al. (Technical Innovations & Patient Support in Radiation Oncology)
We hypothesized that pre-consult patient education videos can improve patient understanding about their diagnosis, lead to high satisfaction and low distress. In this pilot study, we developed a patient education video curriculum for patients with newly-diagnosed anal cancer. Comprehension of key content was evaluated by comparing pre- and post-test scores. Patient satisfaction scores were collected. Patient distress scores (0–10) were collected at the beginning of their consult visit prior to seeing the physician. We found that patient education videos prior to consult improved patient understanding, resulted in high patient satisfaction, and low patient distress at the time of consult.